Peran Orang Tua dan Pemimpin Rohani Bagi Pertumbuhan Iman Generasi Z di Gereja Jemaat Kristen Indonesia Mahanaim Blitar - Luki Imelda; Yusup Rogo Yuono (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
Generation Z is the generation born between 1997 – 2012, who in 2023 will be 11 – 26 years old (Beresford Research). Some of Generation Z in 2024 will be teenagers. During this time, teenagers often face difficult times in finding their identity. Especially in generation Z, who were born in the midst of very rapid developments, especially in the internet era, which requires teenagers to be able to master it well. Along with the positive impacts that occur, negative impacts also affect teenagers today. The challenges and challenges faced by teenagers can have a negative impact on their future success. Therefore, there is a need for mentors around them to direct them. Faith is the basis that generation Z must have to be able to adapt in the search for identity and compete in a very rapid era of development. In this way, the Church plays a very important role in building the growth of faith of generation Z. This faith growth research was carried out at the JKI Mahanaim Church in Blitar City, East Java in order to increase the growth of faith of generation Z in the internet era in Blitar City and form a new concept in the world of pastoral ministries. This research uses a literature study method with a qualitative and descriptive approach. Researchers used James W Fowler's theory of faith growth to determine indicators of Generation Z experiencing faith growth. From the results of this research, it is hoped that Church Leaders and Mentors will pay special attention to the growth of faith and ways to build the faith of Generation Z.